THE IMPACTS OF DISCOVERY LEARNING AND READING INTEREST TOWARD COMPREHENDING TEXT OF STUDENTS - Nurillahwaty, Eka; Sari, Artanti Puspita; Firdaus, Masagus (Premise: Journal of English Education and Applied Linguistics, 2023)
The current research aims to determine the significant influence of discovery learning (DL) and reading interest on comprehending students’ text at SMPN 1 Sembawang. This study selected 64 ninth-grade students from SMPN 1 Sembawa as samples using a two-stage random sampling technique. The quantitative factorial design method was applied in this investigation. The data was acquired via a questionnaire and a test: paired Sample t-test, Independent Sample t-test, and Two Ways ANOVA were used to analyze the data. The result showed that the discovery learning method significantly influenced ninth-grade students’ reading comprehension. Second, there was a significant influence of students’ reading interest toward ninth-grade students’ reading comprehension of folktales. Third, the student’s reading comprehension exam substantially impacted the DL and interest in reading. The result suggested that the discovery learning method and reading interest significantly impacted students’ reading comprehension. The study implies that the DLM helped pupils improve their reading comprehension.